Modulação 2-adrenérgica do remodelamento cardíaco de ratos submetidos a estresse: papel do sistema ubiquitina proteassoma e da apoptose - Conrado, Ricardo de Moura [UNIFESP] (2016)
In the heart, the chronotropic and inotropic effects of catecholamines are mediated by ?1- (?1-AR) and ?2-adrenoceptors (?2-AR), with predominance of the ?1 subtype. Both adrenoceptors are coupled to stimulatory G protein (Gs) - adenylyl cyclase (AC) - cyclic adenosine monophosphate (cAMPc) - cAMP dependente kinase A protein (PKA). ?1-AR overstimulation has cardiotoxic effect, whereas ?2-AR also activates the Gi??-phosphatidilinositol-3-phosphate/kinase B protein pathway. Foot shock stress (ST) alters ?1/?2-AR ratio, reducing ?1-AR and increasing ?2-AR expression. The aim of this work was to investigate if this ST-induced alteration affects the expression of proteins related to the cardiac remodeling, apoptosis or pathological hipertrophy. Data have shown that the mRNA expression of ?1-AR was not altered by ST or by the treatment with ICI 118,551 (ICI). However, there was an interaction between ST and ICI. ?1-AR protein expression was significantly reduced in the ST group as compared to CO and was not altered by ICI. The ?2-AR mRNA expression was not modified by ST or by ICI. However, there was interaction between both treatments. ?-arrestin 2 protein expression was not affected by ST or ICI. Similar result was seen for GRK 2. Rats? treatment with ICI reduced the mRNA expression of Gs, Gi and MuRF1. This last effect was not modified by ST. Similar effect was seen for atrogin-1, E3 ligase, C2 and C5 proteasome. Data presented here suggest that ?2-AR modulates cardiac remodeling by keeping under control the processes of apoptosis, hypertrophy and atrophy. Under stress, its increased expression guarantees such protection by counteracting the cardiotoxic effects triggered by ?1-AR overstimulation.